2011
DOI: 10.1088/0953-8984/23/46/464205
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous superconductivity in organic conductors: the role of disorder and magnetic field

Abstract: Several experimental studies have shown the presence of spatially inhomogeneous phase coexistence of superconducting and non superconducting domains in low dimensional organic superconductors. The superconducting properties of these systems are found to be strongly dependent on the amount of disorder introduced in the sample regardless of its origin. The suppression of the superconducting transition temperature Tc shows clear discrepancy with the result expected from the Abrikosov-Gor'kov law giving the behavi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…27 ). Such measurements could also reveal whether there exist similarities between the AO and the glass-like transition observed in fully deuterated/hydrogenated salts of κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br 82 , and how an inhomogeneous texture of the low temperature phases of these organic salts could explain the strong sensitivity of their superconducting properties to cooling effects 113 . In order to gain more insights into the screening and polarization effects in the (TMTCF) 2 X salts, systematic calculations of the Madelung energy 114 above and below the CO transition temperature, including the polarization effects induced by the anion shift, are required.…”
Section: Discussionmentioning
confidence: 99%
“…27 ). Such measurements could also reveal whether there exist similarities between the AO and the glass-like transition observed in fully deuterated/hydrogenated salts of κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br 82 , and how an inhomogeneous texture of the low temperature phases of these organic salts could explain the strong sensitivity of their superconducting properties to cooling effects 113 . In order to gain more insights into the screening and polarization effects in the (TMTCF) 2 X salts, systematic calculations of the Madelung energy 114 above and below the CO transition temperature, including the polarization effects induced by the anion shift, are required.…”
Section: Discussionmentioning
confidence: 99%
“…5a); b) as an assembly of weakly interacting nanoparticles (Fig. 5b) where the field easily penetrates, and the diamagnetic shielding arises from the sum of individual superconducting nanoparticles 23 .…”
Section: B Superconductivity and Critical Magnetic Fields In (Tmtsf)mentioning
confidence: 99%
“…In presence of such a texture superconductivity is achieved through Josephson coupling between AO superconducting domains through the non ordered regions. The quantitative evolution of T S has been calculated [169] using the dependence of L and l with the cooling rate. It is found that the rate of decrease of T S saturates in agreement with the experimental finding.…”
Section: Texture Of the Ao Phasementioning
confidence: 99%